ORGANOLEPTIC QUALITIES OF BROILER MEAT FED WITH FERMENTED HERBS IN COMMERCIAL RATION - I K. D., JAYA; SUKMAWATI, N. M. S.; LINDAWATI, S. A. (Majalah Ilmiah Peternakan; Vol 28 No 1 (2025): Vol. 28 No. 1 (2025), 2025)
Nowadays, the broiler rearing process uses a lot of chemicals which can cause antibiotic resistance if consumed by humans. An effort that can be implemented is to replace chemicals with herbal ingredients. The target of this research is to examine the impact of providing fermented herbs in commercial rations on the organoleptic quality of broiler meat and to find out the best level preferred by panelists. This research was carried out from July-August 2023 in Banjar Jambe Baleran, Tabanan Regency, Bali. Organoleptic tests were held at the Faculty of Animal Husbandry, Udayana University, Animal Products Technology and Microbiology Laboratory. The fermented herbal medicine used is herbal medicine that is made independently from several ingredients, namely: ginger, white turmeric, ginger, palm sugar, fresh milk, pineapple and naturally fermented water. Completely Randomized Design (CRD) which includes 4 actions and 4 repetitions. For P0 action without herbal medicine, P1 is 2% of the ration weight, P2 is 4% and P4 is 6%. The variables studied in this research are organoleptic quality (aroma, color, tenderness, texture, overall acceptability and taste). The research results showed that giving fermented herbal medicine could increase the panelists’ preference for tenderness, color and overall acceptability with the highest score in the P3 treatment, but had no impact on the texture, aroma and taste. It was concluded that giving fermented herbs could improve the organoleptic quality of broiler meat with the highest level of favorability at 6%.